Análise bibliométrica dos estudos da relação entre fogo e cerrado - Costa, Marcus de Souza (Universidade Federal do Tocantins, 2023)
The Cerrado can be defined as a domain containing different phytophysiognomies, covering about 2 million km2 here in Brazil alone. One of the main characteristics of the Cerrado is its close relationship with fire, which shapes it and influences various ecological processes. Given the vast amount of material on this subject (articles, book chapters, annals) it is expected that some will end up standing out more and adding significant weight to the intellectual structure of the subject. The present work brings a bibliometric analysis through the analysis of citations about what is studied in the relationship between fire and Cerrado. Bibliometric analysis is performed from data obtained from the Web of Science and relies on the help of VOSviewer, a specific software for this type of analysis. The data is analyzed by the algorithm and the documents with the most citations are selected and grouped into clusters. Each document selected by VOSviewer was discussed separately, with emphasis on connections with other documents under discussion. The discussion reveals the relationship between cerrado and fire as a vast subject, with many questions and answers. The documents that stand out the most are related to the Cerrado distribution and the main drivers that control this distribution. CO2 and the consequences of climate change are also protagonists in the most influential documents. Furthermore, even with this vast amount of studies, ecologists are still searching for many answers. This is a point cited by most documents. Therefore, it is necessary to mobilize ecologists to delve even further into the studies of fire in the Cerrado.